Ungkapan Penolakan Bahasa Bugis Pada Interaksi Masyarakat di Kelurahan Botto Kecamatan Lalabata Kabupaten Soppeng - Nurhikma Nurhikma; Syamsudduha Syamsudduha; Andi Fatimah Junus (HUMAN: South Asian Journal of Social Studies, 2023)
Abstract. This study aims to describe the forms and strategies of expressing rejection in the Bugis language in community interaction in Botto sub-district, Lalabata District, Soppeng Regency. This type of research is qualitative with a descriptive research design. The data in this study are oral data in the form of words, clauses, phrases and sentences containing rejection in community interactions in Soppeng district Data collection is carried out by recording, listening, recording and documentation techniques. Based on the results of research and data analysis, forms and strategies of rejection expressions were found. (1) The form of direct rejection expression and the form of indirect refusal expression using command sentences and news sentences. (2) The strategy of expressing rejection found in the study is the strategy of expressing rejection using suggestions, the strategy of expressing rejection with a delay in time, reasons, and the strategy of expressing rejection with apologies Keywords: Rejection expression, form and strategy, bugis language